Peningkatan Usaha Kelompok Tani Hutan Sadar Tani Muda Melalui Pemanfaatan Teknologi, Pemasaran Digital, dan Keuangan, Desa Bojong Murni Kabupaten Bogor - Hermawan, Yanto; Cahyani, Nani; Listari, Sinta; Putri, Melani Faliana; Sucilawati, Sabrinah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This community service program was carried out with the Sadar Tani Muda Forest Farmers Group (KTH) in Bojong Murni Village, Bogor Regency, aiming to strengthen their business capacity through the use of information technology, digital marketing, and financial literacy. The main challenges faced by the group were limited market access, low adoption of digital tools, and weak financial record-keeping. The methods involved training, mentoring, and the implementation of a simple website, social media platforms, and financial recording applications using Excel/Google Sheets. The results indicate a significant improvement in members’ abilities to utilize digital media for product promotion, prepare simple financial reports, and manage their businesses more systematically. Descriptive analysis showed that the variables of digital marketing, information technology utilization, and financial management were rated high to very high, with mean scores of 4.16, 4.11, and 4.23 respectively. The program’s impact was reflected in increased sales, cost efficiency, and members’ awareness of professional business management. These findings highlight that technology-driven interventions and financial literacy enhancement can effectively strengthen farmers’ economic independence while supporting sustainable development goals at the village level Keywords: Community empowerment, information technology, digital marketing, financial literacy, farmer group